(untitled) (Brazilian Journal of Health Research, 2025)
Introduction: Given the advancement of scientific discussions and the growing incorporation of the concept of ableism in academic productions, the following question arose: in what contexts is the term "ableism" used in school settings? Objective: To identify how the concept of ableism is described and applied in the scientific literature. Methods: A systematic search was conducted in four databases — Periódicos CAPES, PePsic, BVS-Psi, and SciELO — using the descriptor "ableism." The inclusion criteria were: national authorship scientific articles, available online, and published between 2021 and 2024. Based on the selected materials, a literature review was carried out focusing on the identification of approaches and interpretations of ableism within the school environment. Results: The analysis reveals significant reflections on the multiple forms of ableism manifestation within educational institutions, both subtly and explicitly. It is observed that, beyond openly discriminatory attitudes, ableism also manifests through gestures and practices that, although seemingly benevolent, perpetuate stigmas and prejudices against people with disabilities. Conclusion: This study may serve as both a warning and a source of information and awareness for society. Observing the school environment reveals various facets of a culture of ableism that values individuals solely based on their physical or mental abilities, overlooking the diversity and complexity of human experience. Thus, it is hoped to contribute to the construction of more inclusive, equitable, and respectful educational spaces.